Contribution of Workload and Compensation to Teacher's Burnout - Masduki Ahmad; Heni Rochimah (AL-ISHLAH: Jurnal Pendidikan, 2021)
This research was conducted to show the contribution of workload and compensation to teacher burnout in Cilacap Regency. The methodology in this study is the quantitative approach with multiple linear regression models. The sample was conducted on 142 teachers in Cilacap Regency. The research instrument is a closed questionnaire on google form based on the Likert scale. Hypothesis testing is obtained from the t-test and the F test. The results show several conclusions: 1) Workload contributes positively and significantly to teacher’s burnout in Cilacap Regency, which means increasing workload will increase teacher’s burnout. 2) Compensation has a negative and significant contribution to teacher work burnout in Cilacap Regency, which means an increase in compensation will decrease teacher work burnout. 3) Workload and compensation contribute to teacher work burnout in Cilacap Regency with a determination coefficient value of 0.439 or 43.9%, which means that workload and compensation contribute together to burnout by 43.9%.